O jeitinho das capixabas : movimento social LGBT e militantes trans do Espírito Santo - Tosta, André Luiz Zanão (2015)
This thesis results from an investigation conducted from 2013 to 2014, in Espírito Santo state. It analyzed the political performance of transgenders (individuals who are self-identified as transsexual and travestis1) according to the identity delimitation of the political movement itself. Based on a descriptive and interpretative investigation proposal, the research has three theoretical elements: (a) the political mobilization usually stems from a “solidarity” feeling existence which comes from a shared experience; (b) the “subject” is the result of the lived experiences, both individual and collective ones; (c) the social movements can be understood as “fields” that generate subjective changes on the subjects as they embody both its structuring and structured logics. In conclusion, it is argued that if the LGBT (and the trans activists) movement’s claims abide by “visibility” and “citizenship” ideals it is necessary to question the meaning of these political struggles on these people’s concrete experiences. Instead of using the simplistic speculation that “identity” and “justice” are the responsible elements of social movements engagement, one should understand how these elements settle down and negotiate among the collective “boards” of supporters and opponents, especially how they become “opportunities” of action and mobilization.